THE USING OF RIDDLES TECHNIQUE TO INCREASE STUDENTS’ VOCABULARY MASTERY FOR THE FIRST GRADE AT MTS PAB 1 HELVETIA - Rafika Purba (Jurnal Mantik Penusa, 2017)
The objective of this research is to know the implementation of riddle technique in students’ vocabulary mastery and to find out whether the improvement of the students’ vocabulary mastery through the riddle technique. This research was conducted at MTs Persatuan Amal Bakti (PAB) 1 Helvetia academic year 2017-2018 as the subject of researcher. The subject of this research were consisted of 49 students of the first grade in class VII-B.The research was conducted with Classroom Action Research. In conducting this classroom action research, the writer divided the action into two cycles. The instrument of collecting data were qualitative data from observation, interview, diary notes, and documentation. Quantitative data were taken from tests, which was carried out in the end of every cycle.Based on the result of this research showed that the students’ score increased from the first meeting namely cycle I until the last meeting namely cycle II. From the counting, the researcher found the mean of pre-test was 46,32, there was 8,16% (4 students) who got points up 75. In the post test cycle I, the mean was 68,67, it was higher than pre-test. There was 46,93% (23 students) who got points up 75 in post test I of cycle I. In the post test cycle II, the mean was 78,87, it was higher than post test I. There was 85,71% (42 students) who got points up 75 in post test I of cycle I. In the other words, the students’ vocabulary mastery was increased. Based on the observation, it showed that the enthusiasm and excitementof the students were also improved.Keyword : Vocabulary, Riddle Technique